Difficulties encountered during the pandemic reported by dentists: A pilot study - Brítez Distéfano, Sonia Concepción (2022)
Objective: To evaluate the economic and psychological repercussions, among other difficulties encountered during the COVID-19 pandemic in a group of dentists. Materials and methods: Cross-sectional descriptive observational study. An online questionnaire was applied to dentists from the “Rigoberto Caballero” Central Police Hospital (HCPRC) of Asunción-Paraguay that was distributed between July and September 2021. It consisted of 32 closed questions distributed in 5 sections: sociodemographic data, economic effects of the pandemic, psychological effects, contagion, and experiences with respect to the clinic. The data were analyzed with the Epi Info version 7 program and the results are represented in tables, the Fisher's exact test and the Chi-square test were also used. Results: 78 dentists participated, 78.2% female, 56.4% from the 35-45 age group. 88.5% reported a decrease in income in private practice and the majority had to resort to another source to be able to cover daily expenses. Most reported having suffered symptoms of anxiety and depression during the pandemic and felt the need to consult a psychiatrist. It was reported an increase in the demand for Personal Protective Equipment (PPE) and an increase in its costs. Almost half of all dentists reported getting COVID-19. Conclusion: The pandemic had a considerable impact on HCPRC dentists, causing financial problems, psychological repercussions and difficulties with prices and a shortage of PPE.